Relative importance of site selection and aftercare for successful reintroduction of the policy species Kosteletzkya pentacarpos. (2nd January 2023) - Corli, Anna; Gerdol, Renato; Orsenigo, Simone; Rossi, Graziano; Abeli, Thomas; Iacumin, Paola; Marchesini, Roberta; Brancaleoni, Lisa
Abstract: Plant translocations have been performed and are ongoing, aimed at establishing long-term resilient and self-sustaining populations. Nevertheless, some of them have not succeeded because of failure in pre- and post-translocation phases such as erroneous site selection and lack of long-term monitoring and adaptive management (i.e. aftercare). This study focused on the relative importance of site suitability and aftercare on the performance of reintroduced populations of Kosteletzkya pentacarpos . This species was studied in two sites representing opposite ends of its ecological niche (freshwater and brackish sites), in the presence of the local vegetation ( Phragmites australis and Juncus sp. pl.) and in its absence. Data on environmental variables, plant growth, ecophysiology and reproductive performance were obtained. Kosteletzkya pentacarpos performed better in the brackish site, exhibiting higher performance especially in the presence of the local vegetation. Conversely, plants growing in the freshwater site had lower performance, despite the removal of the local vegetation. Environmental features of the sites affected species performance more than interactions with co-existing species and site management, highlighting that selection of suitable recipient site is crucial to ensure successful translocation. Aftercare is unlikely to effectively counteract the effect of sub-optimal ecological conditions in terms of plant establishment and performance.